2010
DOI: 10.1186/1471-2296-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Variation in plasma calcium analysis in primary care in Sweden - a multilevel analysis

Abstract: BackgroundPrimary hyperparathyroidism (pHPT) is a common disease that often remains undetected and causes severe disturbance especially in postmenopausal women. Therefore, national recommendations promoting early pHPT detection by plasma calcium (P-Ca) have been issued in Sweden. In this study we aimed to investigate variation of P-Ca analysis between physicians and health care centres (HCCs) in primary care in county of Skaraborg, Sweden.MethodsIn this cross sectional study of patients' records during 2005 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…While some previous studies have shown that the variation at the physician level accounted for about 50% of variation at the practice level [ 21 ], others suggest that the variation at the physician level is more prominent. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…While some previous studies have shown that the variation at the physician level accounted for about 50% of variation at the practice level [ 21 ], others suggest that the variation at the physician level is more prominent. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…The alternative to surgical treatment is active surveillance occasionally combined with medical treatment, for example with bisphosphonates, in order to manage any complications. Controversy remains, however, as to what is the best treatment for patients with those nonclassical symptoms and here is where referral patterns differ . Many patients who would potentially gain from PTX today end up in a grey zone regarding treatment and follow‐up, and an untreated disease may progress silently until complications occur.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by the previous pilot studies in the Valencian Community 12 and all around Spain [13][14][15][16][17][18] a call for data was posted via email. Spanish laboratories willing to participate in the study were invited to fill out an enrollment form and submit their results online.…”
Section: Data Collectionmentioning
confidence: 99%
“…Test requesting inappropriateness is a major issue for a healthcare system 7,8 ; test under requesting results in misdiagnosis, on the other hand, over requesting produces unnecessary expenses, but even physical and psychological patient adverse effects [8][9][10][11] . There is high variability in the request of calcium (S-calcium) and phosphate (S-phosphate), between different regions, and referring physicians [12][13][14][15][16] . In certain areas, S-calcium is under-requested to detect asymptomatic PHPT 14,15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation